Effect of the silica support on the reactivity and polymerization activity of organochromium complexes. - Fu, Anqiu. (University of Ottawa (Canada), 2002)
The effect of the support in heterogeneous catalysis is very important but often poorly understood. The reaction of tetraneopentylchromium(IV) with Sylopol 952, a silica gel used industrially as a carrier for alpha-olefin polymerization catalysts, has been investigated and compared with the previously reported reaction on Aerosil 200, a fumed silica often used to model catalyst supports. Grafting, thermolysis, and metathetical exchange reactions of chromium(IV) neopentylidenes were found to be the same on either Aerosil 200 or Sylopol 952. However, reactivity of the grafted organochromium fragments towards ethylene was found to be quite different on the two supports. The research described in this thesis also explores the polymerization activity of bis(neopentyl)chromium(IV) fragments at higher ethylene pressures than were previously investigated. This result has greatly altered thinking about the nature of the active site for olefin polymerization over surface organochromium fragments. The supported bis(neopentyl)chromium(IV) is no longer believed to require thermal activation to create chromium alkylidene active sites. A possible mechanism is postulated. Propylene polymerization by the Aerosil-supported chromium alkylidene was observed as a slow pseudo-first-order reaction. The kinetics were examined at the gas-solid interface by in situ FTIR spectroscopy and the second-order rate constant compared to those previously measured for ethylene and 1-hexene.
Keywords: Chemistry, Inorganic.